Pioneer years of electron probe microanalysis in Slovenia - Vodopivec, Franc (Kovine zlitine tehnologije, 1997)
Two periods are found in the pioneer years of electrons probe microanalysis (EPMA) in Slovenia: - a longer period up to 1969 when an electron probe microanalyser was put in operation in the Institute of metallurgy in Ljubljana, and - a shorter period after this date until the spreading of EPMA backed by sufficient research achievents demonstrating it wide field of use and the sufficient mastering methodology. The use of EPMA up to 1969 was of marginal extent but not of marginal scientific merit and centred to topics of selective oxydation of alloys of iron with arsenic, cooper, tin and antimony. The interest for EPMA and the conviction that it will greatly improve the quality of the actual research as well as open new topics helped significantly were great. Prof. D. Kolar and his collaborators were among the best prepared and also among the most successfull. With the cooperation of some younger scientists he accomplished several projects which found significant interest in the international research community and were realised thanks to the fast governing of EPMA methaodology. Let us quote only some achievements published up to some years after the putting in operation of EPMA in 1969: - binary phase equilibra diagrams were established for niobium, titanium and circonium carbides with iron, nickel, chromium and cobalt; - binary phase equilibra diagrams were established for uranium sulphide and sulphides of calcium, barium and strontium; - several projects were accomplished with the aim to understand better the microstructure of ferrite ceramics, its sintering process and the effect of microstructure and sintering on magnetic and electrical properties. In binary phase equilibra diagrams solid solubilities and eutectic compositions were determined. Also because of the contribution of prof. D. Kolar the pioneer period of EPMA in Slovenia was short and successful and helped to strenghten it as one of the base scientific facility for research ofsolid materials on microstructure level.
Keywords: elektronska mikroanaliza; fazni diagrami; karbidi; sulfidi; zgodovinski pregledi